Interreligious Education: Development of Religious Moderation in The Education Sector - Daimah Daimah Daimah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Recently there have been many cases of intolerance in educational institutions, such as the state school policy that requires all students to wear Muslim uniforms including non-Muslim students, there have been cases of terror experienced by non-Muslim students by Rohis organizations, and several other cases that have occurred in educational institutions. This in turn will damage the harmony between religions, and eliminate attitudes of respect for the truth of other religions and conflict with the principle of diversity which is the motto of the pluralistic Indonesian state. This research is qualitative literature research with a socio-cultural approach. The results of the study show that interfaith education is part of intercultural education which aims to build understanding, tolerance an,d social attachment to actively form relations between people of different religions. Interfaith education is positioned as an additional supplement to support and enrich the teaching practice of Religious Education in educational settings. This is in line with the new policy of implementing the Pancasila Student Profile in the Independent Curriculum. The existence of Pancasila Student Profile policy in an independent curriculum is expected to instill tolerance values in the life of diversity in the world of education.